PERFIL EPIDEMIOLÓGICO DOS PACIENTES DO CONSULTÓRIO DE NUTRIÇÃO DA UNIJUÍ - Boff, Charles J. T.; Wassermann, Emanuele R.; Zanetti, Carolina; Treuherz, Luciane C.; Dessuy, Daiana V.; Franz, Ligia B. B. (Salão do Conhecimento, 2013)
Resumo